DEVELOPMENT OF QUALITY CONTROL PARAMETERS FOR STANDARDIZATION OF A NOVELMUCILAGE OBTAINED FROM OKRA (ABELMOSCHUS ESCULENTUS (L.) MOENCH) FRUIT - DAS, SOMA; GHOSH, ANANYA; DAS, RUSHAM; NANDI, GOURANGA; GHOSH, LAKSHMI KANTA (International Journal of Current Pharmaceutical Research, 2021)
Objective: The main objective was to focus on qualitative and quantitative analysis of isolated okra mucilage by High-performance Thin Layer Chromatography to set up the quality control parameters for the isolated mucilage. Methods: High-performance thin-layer chromatography (HPTLC) were applied for the identification of components present in methanolic and ethanolic fruit extract of okra at 254 nm and 356 nm. Quantitative analysis of amino acid ascorbic acid and total polyphenol content was determined. Results: The results showed that the yield percentage for methanolic and ethanolic fruit extract of the okra fruit mucilage was found to be 13.5 and12.5% respectively. HPTLC determination of methanolic and ethanolic okra fruit extract showed the presence of 8 components with Rf values in the range of 0.14 to 0.62 and 0.14 to 0.54 respectively when detected at wavelengths 254 nm and at 356 nm. The total amino acid in okra fruit methanolic extract was found to be 11.45%w/w. The ascorbic acid content in methanolic okra fruit extract and ethanolic okra fruit extract was found to be 0.24 %w/w and 0.18% w/w respectively. The total phenolic contents (tannic acid equivalents, mg/g) in the methanolic and ethanolic okra fruit extracts were calculated to be 4.6 % w/wand 5.3% w/w respectively. Conclusion: The data revealed dual benefits like it can act as a potential novel functional ingredient with health-promoting application due to the presence of ascorbic acid and total phenolics contents and at the same time the data provided guidelines for quality control parameters for the isolated okra fruit